Sustainability Marketing: Digital Marketing pada Kinerja Pemasaran Pariwisata Melalui Inovasi Produk - Arief, Muh.; Sismar, Andi (Jurnal Manajemen STIE Muhammadiyah Palopo, 2025)
The purpose of this study was to determine: the effect of digital marketing on marketing performance; the effect of digital marketing on product innovation; the effect of product innovation on marketing performance; the effect of product innovation in mediating the relationship between digital marketing and marketing performance. This study uses a quantitative method. The population of this study were tourism MSME actors in the Sorong Regency area of Southwest Papua. The sampling technique was saturated. So the total sample in this study was 64 people. Data analysis in this study was carried out using the Structural Equation Modeling (SEM) method to test the formulated hypotheses. Each hypothesis was analyzed with the help of Partial Least Square (PLS) software version 3.0 to spread the relationship between the variables studied. The activities include: distributing questionnaires, collecting, editing, and analyzing data and drawing conclusions. The results of this study reveal that digital marketing has a positive and significant effect on marketing performance, in addition digital marketing has a positive and significant effect on product innovation, in addition product innovation has a positive and significant effect on marketing performance, furthermore digital marketing has a positive and significant effect on marketing performance mediated by product innovation.